Stability Analysis of Dapodik Website: A WebQual Efficiency Model Approach - Mulyono, Hadi; Wardoyo, Ari Eko; Handayani, Luluk (Sinkron : jurnal dan penelitian teknik informatika, 2024)
This study aims to provide a deeper understanding of how Dapodik can play a role in supporting efficiency and improving the quality of education at the primary level. The research methodology adopts qualitative research design using WebQual 4.0 model. A qualitative approach was chosen to gain an in-depth understanding of user experience regarding the stability and effectiveness of Dapodik in the management of educational data. This study involved participants from two leading elementary schools in Kabupaten Jember, Jember Lor 3 State Elementary School and Al Furqon Elementary School. In its analysis, the research instrument covers three main aspects. The findings show fluctuations in usability scores that reflect application access and performance instability. Although Dapodik shows a good focus on search engine optimization with high SEO value and best practices, improvements to the Largest Contentful Paint (LCP) and page structure are needed to improve stability and responsiveness. The results of operator interviews show the adequacy of Dapodik information, however, more attention is needed in understanding the features of the application. User service responsiveness can be improved by minimizing delays in providing guidance. Suggestions for improvement include stabilization of applications and improved understanding of features, while continued research can explore the positive impact of Dapodik in the context of student learning in various educational environments.